2021
DOI: 10.1038/s41598-021-88885-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial composite coatings of MgB2 powders embedded in PVP matrix

Abstract: Three commercial powders of MgB2 were tested in vitro by MTS and LDH cytotoxicity tests on the HS27 dermal cell line. Depending on powders, the toxicity concentrations were established in the range of 8.3–33.2 µg/ml. The powder with the lowest toxicity limit was embedded into polyvinylpyrrolidone (PVP), a biocompatible and biodegradable polymer, for two different concentrations. The self-replenishing MgB2-PVP composite materials were coated on substrate materials (plastic foil of the reservoir and silicon tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…4a, b , Nano-MgB 2 exhibited excellent antibacterial activity at a low concentration at around 12.5 μg/mL, whereas H 3 BO 3 + Mg 2+ group exhibited little or no antibacterial effect against P. aeruginosa at the same concentration. This antibacterial effect of our synthesized Nano-MgB 2 was dramatically stronger than that of commercial MgB 2 powders 37 , and was comparable to the effects of gentamicin, amikacin, ciprofloxacin, levofloxacin, and better than imipenem, meropenem, ceftazidime, cefepime, ampicillin+sulbactam, aztreonam (Supplementary Fig. 16a ).…”
Section: Resultsmentioning
confidence: 62%
“…4a, b , Nano-MgB 2 exhibited excellent antibacterial activity at a low concentration at around 12.5 μg/mL, whereas H 3 BO 3 + Mg 2+ group exhibited little or no antibacterial effect against P. aeruginosa at the same concentration. This antibacterial effect of our synthesized Nano-MgB 2 was dramatically stronger than that of commercial MgB 2 powders 37 , and was comparable to the effects of gentamicin, amikacin, ciprofloxacin, levofloxacin, and better than imipenem, meropenem, ceftazidime, cefepime, ampicillin+sulbactam, aztreonam (Supplementary Fig. 16a ).…”
Section: Resultsmentioning
confidence: 62%
“…Despite top-down techniques in general offer better controllability over surface roughness with higher reproducibility, bottom-up approaches are still more popular as they are cheaper, easier to apply, and offer higher scalability. Although, the advanced examples of rough surfaces for wetting-related functional applications are composites (consisting of a matrix-/support-and one or more roughening filler materials) [63,64], monolithic systems also can be prepared by topdown techniques [65], filtrate deposition [51], foam-sintering [66] or templating methods [67].…”
Section: Utilization and Elaboration Of Surface Texturementioning
confidence: 99%
“…MgB 2 can be prepared by a variety of methods, including spark plasma sintering (SPS) [ 26 , 27 , 28 , 29 , 30 , 31 ]. Our research group has recently reported for the first time in the scientific literature the potential for the antimicrobial applications of MgB 2 materials (powders and biodegradable coatings based on polyvinylpyrrolidone) for the clinical field and for combating the negative impact of microbial colonization in different environments, as with the biodeterioration of heritage buildings [ 26 , 32 , 33 , 34 , 35 ]. We have previously shown that the antimicrobial activity of MgB 2 powders depends on the fabrication process (e.g., MgB 2 powders produced by reactive liquid infiltration (RLI) show superior performance to commercial powders) as well as their purity, microstructure, and pH behavior in water.…”
Section: Introductionmentioning
confidence: 99%